Review of open-field vegetable automatic following transportation technology and equipment - Zhang, Jianfei; Tang, Jincheng; Song, Zhiyu; Liu, Jianbo; Ning, Xiaofeng; Cao, Guangqiao (International Journal of Agricultural and Biological Engineering, 2026)
The vegetable industry is the largest sector within China’s planting industry. The integration of modern informationtechnologies such as big data and the Internet of Things (IoT) with agricultural equipment has facilitated the intelligentupgrading and transformation of the vegetable industry. This paper addresses the lack of automatic field transportationequipment for open-field vegetables. Around the main production scenarios of open-field vegetables, this paper summarizes theresearch status of field transportation equipment at home and abroad, and compares the characteristics of oil-powered andelectric transporters. The paper also points out that the automatic following technology of field transportation equipment is acrucial technology for achieving coordinated harvesting and transportation. It proposes that automatic following technology isprimarily realized through navigation and positioning technology and path tracking technology, and elaborates on theapplication research status of both. Based on this, the paper outlines the current application of field transporters in China,identifying issues such as poor integration of agricultural machinery and agronomy, poor adaptability of transport vehicles,poor navigation and positioning stability, insufficient environmental adaptability of path tracking algorithms, and immaturemulti-machine coordination technology for field transportation. The future development trends of standardized vegetableplanting, optimization of transportation equipment structure, precision and intelligence of automatic following technology,multi-machine collaborative operation, and emphasis on energy utilization and environmental protection are proposed. Finally,the paper summarizes the applicable scenarios of field transportation equipment, navigation and positioning modes, and pathtracking algorithms in conjunction with the content of the full text. Keywords: vegetables, field transport, positioning technology, automatic following technology, path tracking DOI: 10.25165/j.ijabe.20261904.9963 Citation: Zhang J F, Tang J C, Song Z Y, Liu J B, Ning X F, Cao G Q. Review of open-field vegetable automatic following transportation technology and equipment. Int J Agric & Biol Eng, 2026; 19(4): 1–15.